Syntheses of new tuberculosis inhibitors promoted by microwave irradiation. (May 2014) - De Rosa, Maria; Gising, Johan; Odell, Luke R.; Larhed, Mats
Abstract Tuberculosis (TB) represents a major public health problem. The growing number of (extensively) multi-drug resistance cases indicates that there is an urgent need for discovery of new anti-TB entities, addressed towards new and specific targets, and continuous development of fast and efficient synthetic strategies to access them easily. Microwave-assisted chemistry is well suited for small-scale laboratory synthetic work, allowing full control of reaction conditions, such as temperature, pressure, and time. Microwave-assisted high-speed organic synthesis is especially useful in the lead optimization phase of drug discovery. To illustrate the advantages of modern microwave heating technology, we herein describe applications and approaches that have been useful for the synthesis of new drug-like anti-TB compounds.